The Case for an Ethical Black Box - Winfield, Alan F. T.; Jirotka, Marina (Towards Autonomous Robotic Systems, 2017)
This paper proposes that robots and autonomous systems should be equipped with the equivalent of a Flight Data Recorder to continuously record sensor and relevant internal status data. We call this an ethical black box. We argue that an ethical black box will be critical to the process of discovering why and how a robot caused an accident, and thus an essential part of establishing accountability and responsibility. We also argue that without the transparency afforded by an ethical black box, robots and autonomous systems are unlikely to win public trust.